Language, Agency, and Intercultural Encounters: The Perspectives of Development Volunteers’ Receiving Partners in Jalisco, Mexico - Jabłońska-Bayro, Joanna (INSTED: Interdisciplinary Studies in Education & Society, 2025)
This article examines the involvement of local actors in international volunteering settings, exploring the perspectives of receiving partners of the German weltwärts program in Jalisco, Mexico. It concentrates on local partners’ assistance with volunteers’ local language learning, which tends to be commonly envisioned as a spontaneously acquired by-product of the volunteering sojourns and overlooked as an intentional and collective effort. The study also provides insight into the significance the respondents attribute to language-related activities in shaping volunteers’ and their own positioning during the sojourns. By supporting volunteers’ Spanish acquisition and reflecting on this process, the receiving partners acknowledge themselves as active organizers of volunteering spaces; they exert agency in a context of postcolonial assumptions that still shape the institutional architecture of development volunteering programs and tend to portray the local hosts as passive aid receivers. Their agentive perspective enables a nuanced quotidian reflection on volunteering as an intercultural encounter, highlighting the essential role of language in it.